2000
DOI: 10.1002/1097-0010(200007)80:9<1307::aid-jsfa638>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of domesticated and wildRubus species

Abstract: The antioxidative capacities of a number of Rubus species of varied pigmentation have been investigated. In addition, total phenol, anthocyanin and ascorbic acid contents have been determined. Two methods to assess the antioxidant potential of fruit juices have been used. The antioxidant capacities of the fruit ranged from 0 to 25.3 mmol Trolox equivalents g À1 (TEAC) or from 190 to 66 000 mmol l À1 ferric reducing antioxidant power (FRAP). Ascorbic acid contributes only minimally to the antioxidant potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
271
4
6

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(317 citation statements)
references
References 23 publications
36
271
4
6
Order By: Relevance
“…Using a standard, the main cyanidin derivative peak was identified as cyanidin -3 -O -glucoside. The highest cyanidin concentrations were detected in Guarani and Caingangue cultivars (about 150 mg.100 g -1 ), values higher than those detected for domestic and wild species grown in China (1-118 mg.100 g -1 ) (DEIGHTON et al, 2000). Also, data shown for blackberry fruits are superior to anthocyanin contents found in other red fruits, such as strawberry (30 to 60 mg.100 g -1 , CORDENUNSI et al, 2003), purple Surinam cherry (16.23 mg.100 g -1 , LIMA et al, 2005) or acerola (3.79 to 59.74 mg.100 g -1 , LIMA et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a standard, the main cyanidin derivative peak was identified as cyanidin -3 -O -glucoside. The highest cyanidin concentrations were detected in Guarani and Caingangue cultivars (about 150 mg.100 g -1 ), values higher than those detected for domestic and wild species grown in China (1-118 mg.100 g -1 ) (DEIGHTON et al, 2000). Also, data shown for blackberry fruits are superior to anthocyanin contents found in other red fruits, such as strawberry (30 to 60 mg.100 g -1 , CORDENUNSI et al, 2003), purple Surinam cherry (16.23 mg.100 g -1 , LIMA et al, 2005) or acerola (3.79 to 59.74 mg.100 g -1 , LIMA et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Species of the Rubus genus are known as natural sources of anthocyanins with high antioxidant effect (DEIGHTON et al, 2000). Due to the increasing interest in blackberry consumption and the knowledge that the nutritional composition varies according to the cultivar, this work aimed at evaluating the phenolic and anthocyanin content, antioxidant capacity and physicochemical quality of five blackberry cultivars grown in Brazil.…”
mentioning
confidence: 99%
“…The TP content was determined according to the Folin-Ciocalteu method (Deighton, Brennan, Finn, & Davies, 2000;Singleton & Rossi, 1965). However, a drawback with the Folin-Ciocalteu approach is that compounds such as fructose, amino acids and ascorbic acid can contribute to the TP content.…”
Section: Determination Of Total Phenolic (Tp) Contentmentioning
confidence: 99%
“…The ferric reducing power of the leek extracts was determined using the method of Deighton et al (2000). Briefly, a 100 ll aliquot of the leek extract (diluted 2Â) was added to 900 ll of FRAP reagent.…”
Section: Ferric Reducing Antioxidant Potential (Frap) Assaymentioning
confidence: 99%
“…Contribution of phenolic compounds is one of the mechanisms of the overall antioxidant activities. This mainly due to their redox properties involve in the plant material [46]. However, Pearson correlation showed that there was a weak positive relationship (r=0.4713) found for antioxidant activity assayed by β-carotene bleaching assay with TPC.…”
Section: Total Phenolic Contentmentioning
confidence: 99%